Theoretical foundation engineering - Das, Braja M., 1941- (Developments in geotechnical engineering, 1987)
Theoretical Foundation Engineering provides up-to-date, state-of-the-art reviews of the existing literature on lateral earth pressure, sheet pile walls, ultimate bearing capacity of shallow foundations, holding capacity of plate and helical anchors in sand and clay, and slope stability analysis. The discussion of the ultimate bearing capacity of shallow foundations is the most comprehensive presentation on the subject to be found anywhere, and the review of earth anchors is unique to this book. In addition, each chapter includes several topics which have never appeared in any other book. The treatment is primarily theoretical and does not in any way compete with existing foundation design books. This is the only textbook of its kind. Not only will it be welcomed by teachers and first-year graduate students of geotechnical engineering, but it will be a useful reference for graduate students and consultants in the the field, as well as being a valuable addition to any civil engineering library.